Numerical simulation of natural convection and boil-off in a small size pressurized LNG storage tank. (12th July 2020) - Ferrín, J.L.; Pérez-Pérez, L.J.
Highlights: A CFD analysis of the flow and boil-off within a small size LNG tank is presented. Realistic values for the material properties are used. Natural convection flow structures are obtained for various filling levels. The conjugate heat transfer problem is solved to assess the influence of the insulation thickness Filling level is shown to strongly influence boil-off and stratification profiles. Abstract: A numerical simulation of the flow of LNG stored in a small-sized cylindrical tank is presented. The main scope of this work is to characterize the heat ingress to the tank as well as the boil-off rate, depending on the filling level and the insulation layer thickness. The tank is assumed to be in a state of inactivity, such that the fluid phases are initially quiescent and are not released to the exterior. The proposed mathematical model consists of a conjugate heat transfer problem coupled with the SST K − ω turbulence model for the fluid phases. The free surface separating liquid and vapor in the tank is tracked using the Volume of Fluid method (VOF). The model is solved using the software ANSYS Fluent. It is shown that the filling level of the tank substantially influences the boiling rate and the degree of stratification, as well as the flow structures generated by free convection. The relation among the insulation thickness and total heat leak is established, showing that the obtained increased heat ingress due to lower insulation thickness values leads to a rise in pressurization and boil-off rates.